Orange passion fruit (Passiflora caerulea L.) as a new raw material for acetic fermentation: evaluation of organic acids and phenolic profile, in vitro digestion, and biological activities - da Silva Monteiro Wanderley B.R. (2024)
© 2024 Society of Chemical Industry.BACKGROUND: This study evaluated for the first time the potential of orange passion fruit as a base for alcoholic and acetic fermentations, with a view to assessing its profile of organic acids and polyphenols, in vitro digestion, and biological activities. RESULTS: In terms of aliphatic organic acids, malic acid was the majority in the wine (3.19 g L−1), while in the vinegar, it was acetic acid (46.84 g L−1). 3,4-Dihydroxybenzoic acid (3,4-DHB) was the major phenolic compound in the wine and vinegar samples (3443.93 and 2980.00 μg L−1, respectively). After the in vitro gastrointestinal simulation stage, the wine showed high bioaccessibility for the compounds sinipaldehyde (82.97%) and 2,4-dihydroxybenzoic acid (2,4-DHBA, 81.27%), while the vinegar exhibited high bioaccessibility for sinipaldehyde (89.39%). Through multivariate analysis, it was observed that 3,4-DHB was highly concentrated in the different digested fractions obtained from the wine. In contrast, in the vinegar, the stability of isorahmenetin and Quercetin 3-o-rhamnoside was observed during the in vitro digestion simulation. Lastly, the vinegar stood out for its inhibition rates of α-amylase (23.93%), α-glucoside (18.34%), and angiotensin-converting enzyme (10.92%). In addition, the vinegar had an inhibitory effect on the pathogenic microorganisms Salmonella enteritidis, Escherichia coli, and Listeria monocytogenes. CONCLUSION: Orange passion fruit has proved to be a promising raw material for the development of fermented beverages. Therefore, this study provides an unprecedented perspective on the use and valorization of orange passion fruit, contributing significantly to the advancement of knowledge about fermented products and the associated nutritional and functional possibilities. © 2024 Society of Chemical Industry.